Assessing Shariah Compliance in Gift-Giving Practices: A Systematic Literature Review of Fatwa No. 86/DSN-MUI/XII/2012 within Islamic Financial Institutions (TAWAZUN: Journal of Sharia Economic Law, 2025)
This study aims to evaluate the implementation of DSN-MUI Fatwa No. No.86/DSN-MUI/XII/2012 on gift-giving practices within Islamic financial institutions (IFIs). This study used a Systematic Literature Review (SLR) approach. Data was collected on 10/11/2024 from Google Scholar using PoP software and the PRISMA framework. The research analyzes 32 documents, consisting of peer-reviewed journal articles and undergraduate theses. Results show that 47o% of the reviewed studies expose adherence to the fatwa, while 53% reveal forms of non-compliance. Common violations include the use of monetary gifts, habitual gift-giving expectations, and promises made at the inception of contracts. These findings suggest a persistent gap between Shari’ah directives and actual practices across various IFIs. The prevalence of undergraduate theses indicates active academic interest, yet also signals the need for greater methodological rigor and more scholarly contributions at the peer-reviewed level. These results imply a need to improve Shari’ah literacy, enhance institutional supervision, and develop stronger regulatory enforcement.